A proteomic meta-analysis refinement of plasma extracellular vesicles - Milene C. Vallejo; Soumyadeep Sarkar; Emily C. Elliott; Hayden R. Henry; Samantha M. Powell; Ivo Diaz Ludovico; Youngki You; Fei Huang; Samuel H. Payne; Sasanka Ramanadham; Emily K. Sims; Thomas O. Metz; et al. (Scientific Data, 2023)
Abstract Extracellular vesicles play major roles in cell-to-cell communication and are excellent biomarker candidates. However, studying plasma extracellular vesicles is challenging due to contaminants. Here, we performed a proteomics meta-analysis of public data to refine the plasma EV composition by separating EV proteins and contaminants into different clusters. We obtained two clusters with a total of 1717 proteins that were depleted of known contaminants and enriched in EV markers with independently validated 71% true-positive. These clusters had 133 clusters of differentiation (CD) antigens and were enriched with proteins from cell-to-cell communication and signaling. We compared our data with the proteins deposited in PeptideAtlas, making our refined EV protein list a resource for mechanistic and biomarker studies. As a use case example for this resource, we validated the type 1 diabetes biomarker proplatelet basic protein in EVs and showed that it regulates apoptosis of β cells and macrophages, two key players in the disease development. Our approach provides a refinement of the EV composition and a resource for the scientific community.